The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1007/bf02406279
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in cineradiographic assessment of pharyngeal function during swallow

Abstract: Abstract. Cineradiographic examinations of 72 patients with dysphagia and normal or abnormal studies demonstrating a range of pharyngeal dysfunctions during swallowing were retrospectively reviewed indcpendently by six radiologists. The interobserver variability was then assessed. There was high concordance for the assessment of contrast medium reaching into the trachea, absent pharyngeal constriction, and the presence of Zenker divcrticula. The concordance was less for normal pharyngeal function as well as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
2
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 5 publications
2
33
2
1
Order By: Relevance
“…35,36 Reliability ratios in 1 study were highest for aspiration, particularly for solids, and lowest for functional swallowing components. 36 Levels of agreement in ratings correlate with assessor experience 37 and improve with group discussion among assessors 38 ; similar methods of training to criteria may form a way to improve reliability. 35 …”
Section: Videofluoroscopymentioning
confidence: 99%
“…35,36 Reliability ratios in 1 study were highest for aspiration, particularly for solids, and lowest for functional swallowing components. 36 Levels of agreement in ratings correlate with assessor experience 37 and improve with group discussion among assessors 38 ; similar methods of training to criteria may form a way to improve reliability. 35 …”
Section: Videofluoroscopymentioning
confidence: 99%
“…The issue of interrater variability in assessing dynamic images of swallowing has been addressed by Ekberg et al [4], Gibson and Phyland [5], and Wilcox et al [6]. These studies all demonstrated the variability in interpretation of videofluoroscopic images of swallowing.…”
mentioning
confidence: 96%
“…Thus, the utility of VFSS must be established for the good of both patients and providers. However, no studies have been performed that rigorously examine intrarater reliabilities in VFSS, although there are two existing reports on some aspects of interrater reliability [9,10]. This lack is especially important given the subjective methods of evaluating VFSS.…”
mentioning
confidence: 99%
“…Ekberg et al [9] reported interobserver variability in cineradiographic assessment of pharyngeal function during swallowing. Examinations of 72 patients with dysphagia were reviewed retrospectively and independently by 6 radiologists.…”
mentioning
confidence: 99%